2017
DOI: 10.1016/j.envpol.2016.11.056
|View full text |Cite
|
Sign up to set email alerts
|

Radical change of Zn speciation in pig slurry amended soil: Key role of nano-sized sulfide particles

Abstract: Spreading livestock manure as fertilizer on farmlands is a widespread practice. It represents the major source of heavy metal(loid)s (HM) input in agricultural soils. Since zinc (Zn) is present at high concentrations in manure, it poses special environmental concerns related to phytotoxicity, groundwater contamination, and introduction in the food chain. Therefore, investigations on the fate and behavior of manure-borne Zn, when it enters the soil environment, are necessary to predict the environmental effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 49 publications
(55 reference statements)
3
37
1
3
Order By: Relevance
“…Zn sulfides have already been observed in OW 6,18 and were found to be nanostructured only in sewage sludge 29 and pig slurry. 9 Batch experiments in which the physicochemical conditions were similar to those of OW suggested the occurrence of a Zn sulfide nanoparticulate state. Indeed, Lau et al 30 suggested that the high OM content of OW hinders Zn sulfide crystal growth, which would lead to the formation of Zn sulfide nanoparticles.…”
Section: Zinc Speciation In Rawmentioning
confidence: 98%
“…Zn sulfides have already been observed in OW 6,18 and were found to be nanostructured only in sewage sludge 29 and pig slurry. 9 Batch experiments in which the physicochemical conditions were similar to those of OW suggested the occurrence of a Zn sulfide nanoparticulate state. Indeed, Lau et al 30 suggested that the high OM content of OW hinders Zn sulfide crystal growth, which would lead to the formation of Zn sulfide nanoparticles.…”
Section: Zinc Speciation In Rawmentioning
confidence: 98%
“…Normalization and data reduction were performed according to standard methods (Doelsch et al, 2006) using Athena software (Ravel and Newville, 2005). A library of Zn reference compound spectra, described elsewhere (Formentini et al, 2017; was used to identify Zn species in the samples. Details on the fitting procedure and results are given in SI (Text S3, Figure S3 (a, b) and Table S2).…”
Section: Exafs Spectra Acquisition and Analysismentioning
confidence: 99%
“…Very few studies have assessed the fate of this species in the soil after OW spreading. Formentini et al 21 showed that after spreading of pig slurry, in which nano-ZnS accounted for 100% of the Zn speciation, on a clay soil, all the Zn accumulated in the top 30 cm and was distributed between Zn-OM (41%), Zn-kaolinite (38%) and Zn-FeOx (23%). Zn applied to the soil via pig slurry spreading was no longer present in the form of nano-ZnS.…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…18 For instance, different toxicity mechanisms have been described when Escherichia coli were exposed to nanoparticulate ZnO or dissolved Zn. 19 Recent studies using X-ray absorption spectroscopy (XAS) have shown that part of Zn is present as zinc sulfide (ZnS) in raw OWs 20,21 and digestates. 20,[22][23][24][25][26] This technique is thus suitable to determine Zn speciation in a complex matrix such as OW.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation